2016
DOI: 10.1002/jbm.b.33690
|View full text |Cite
|
Sign up to set email alerts
|

Response of duplex Cr(N)/S and Cr(C)/S coatings on 316L stainless steel to tribocorrosion in 0.89% NaCl solution under plastic contact conditions

Abstract: Two duplex coatings, Cr(N)/S and Cr(C)/S, were deposited on 316L stainless steel by magnetron sputtering. The effectiveness of these duplex coatings in improving the tribocorrosion behaviour of medical alloys under elastic contact conditions has been demonstrated in a recent publication. The present work focused on the response of these duplex coatings to tribocorrosion under plastic contact conditions. Tribocorrosion tests were conducted in 0.89 % NaCl solution at 37 o C at an initial contact pressure of 740 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Mechanical wear may also be accelerated due to increased metal dissolution. This is the phenomenon of tribocorrosion, which has been increasingly studied during the past two decades [8][9][10][11]. These studies have identified the complex phenomena involved and the effect of wear on the electrochemical response of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical wear may also be accelerated due to increased metal dissolution. This is the phenomenon of tribocorrosion, which has been increasingly studied during the past two decades [8][9][10][11]. These studies have identified the complex phenomena involved and the effect of wear on the electrochemical response of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Such a ball-cratering technique has been widely used for measuring the thickness of thin coatings. It has recently been employed to aid in the examination of coating deformation beneath a wear track [29].…”
Section: Methodsmentioning
confidence: 99%
“…Caha's research determined that, although the TiN coating did not enhance the tribocorrosion resistance of Ti-12Nb alloy due to the coating delaminating, applying a ZnO layer on top of the TiN coatings significantly improved performance by increasing microhardness and providing a robust physical barrier [75]. CrN and CoCrMo carbon S-phase layers were systematically studied by Bertram Mallia's group [76][77][78]. Among these, CrN/S coatings on 316L demonstrated remarkable tribocorrosion resistance, attributed to their high hardness and substrate adhesion.…”
Section: Deposition From Solutionsmentioning
confidence: 99%